KONSERVASI FLORA, TANAH DAN SUMBERDAYA AIR EMBUNG-EMBUNG DI TIMOR BARAT PROVINSI NUSA TENGGARA TIMUR (STUDI KASUS ’EMBUNG’ OEMASI-KUPANG DAN ’EMBUNG’ LEOSAMA-BELU) - Wahyu Widiyono (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2008)
Conservation of flora, soil and water resources are very important to manage‘embung’ ecosystem, in West Timor Island. Generally, ‘embung’ watersheds in this area are degraded, and consequently resulted high runoff and erosion rate; and at the same time, ‘embung’ water has not been used efficiently yet. To conserve ‘embung’ ecosystem, three methods can be applied, i.e.: 1). Flora conservation by using priority of local species; 2). Soil conservation by usingvegetative methods; and 3). Water resources conservation in watershed area by combining flora and soil conservation; and increasing water used efficiency by using intermediate technology.